Data Delivery Implementation on River Flow Control System Prototype Using HTTP - Ichsan, Mochammad Hannats Hanafi; Akbar, Sabriansyah Rizqika; Aji, Hamdan Malik Satriyo; Setiawan, Eko; Batubara, Othman Mirizi (Journal of Information Technology and Computer Science, 2023)
Data transmission is one of the most essential components in a critical system. One of them is to control the river water canal. Previous research related to water canal monitoring has been carried out, but the data is still local. This research implements a water canal with one main river with three tributaries/river branches where the three tributaries have different area conditions. In this research, the process of sending data from the sensor node (Control Flow System) to the master node (Control station) to the cloud server to be displayed on a website. The microcontroller used for the main processor and as a data-sending device is the ESP8266 and the cloud server used is ThingSpeak. This research succeeded in implementing HTTP for the process of sending data. The HTTP protocol is suitable for the process of data delivery. Sending data on the Control Flow System to the Control Station was successfully sent optimally at a distance of 3 meters with the "Good" classification according to the TIPHON standard. Meanwhile, the average data is sent from the Control Station to the cloud server in about 44 seconds.